Young men’s perspectives on expressing problems affecting their mental health to family and friends in Ehlanzeni district, Mpumalanga province - Phenyo Molokoane; Mahlatse Modipane (Journal of Men's Health)
Background: Worldwide, over 1 in 10 individuals are experiencing some form of mental health issue, including depression, anxiety, schizophrenia and bipolar disorders. South Africa ranks eighth globally for suicide rates, with 450 men taking their own lives every month. This research sought to investigate the views of young men regarding expressing issues impacting their mental well-being with family and friends in the Ehlanzeni district of Mpumalanga province, South Africa. Methods: The investigators utilized a qualitative research approach and implemented a non-probability purposive and convenience sampling technique. A group of sixteen men between the ages of 23 and 35 were interviewed, and the findings were examined using inductive thematic analysis. Results: The study reveals that fear of stigma, masculinity norms and societal expectations are the main reasons why at times, men are unable to talk to their families and friends about problems that affect their mental health. Others have reported that emotional support from family and friends encourages them to speak up. Conclusions: It is increasingly evident that young men face a range of challenges, many of which can deeply affect their mental well-being and overall life satisfaction. This evidence highlights several important areas for improvement in how mental health services are designed and delivered. Therefore, the paper concludes , that gender-specific intervention services designed for men are necessary, and it is essential to incorporate gender considerations to adequately meet the mental health needs of men.